Glutamate Carrier Involvement in Mitochondrial Dysfunctioning in the Brain White Matter - Hillen, Anne E. J.; Heine, Vivi M. (Frontiers in Molecular Biosciences, 2020)
Glutamate homeostasis is an important determinant for health of the central nervous system. Mitochondria play crucial roles in glutamate metabolism, especially in processes with a high energy demand such as action potential generation. Mitochondrial glutamate carriers and aspartate-glutamate carriers regulate the transport of glutamate from the cytoplasm across the mitochondrial membrane, which is needed to control energy demand, lipid metabolism, and metabolic activity including oxidative phosphorylation and glycolysis. Dysfunctions in these carriers are associated with seizures, spasticity, and/or myelin deficits, all of which are associated with inherited metabolic disorders. Since solute carrier functioning and associated processes are cell type- and context-specific, selective vulnerability to glutamate excitotoxicity and mitochondrial dysfunctioning is expected. Understanding this could offer important insights into the pathomechanisms of associated disorders. This perspective aims to explore the link between (aspartate-)glutamate carrier functions and their role in metabolic disorders, with a focus on a subclass of lysosomal storage disorders called leukodystrophies.